Discotheques, Magazines and Plexiglas: Superstudio and the Architecture of Mass Culture - Ross K. Elfline (Footprint)
This article considers the groundbreaking works of the Italian Radical Architecture collective Superstudio (active 1966–80) with an eye to their complex and contradictory relationship to popular culture. Superstudio’s early pronouncements stating their abstention from building presaged their decision to investigate the radical potential of different non-tectonic mediums culled from consumer culture.